Immediate and long-term results of laparoscopic hernioplasty in inguinal hernias with and without mesh endoprosthesis fixation - O. V. Zaitsev; A. V. Koshkina; D. A. Khubezov; V. A. Yudin; V. V. Barsukov; I. Yu. Bragina (Вестник хирургии имени И.И. Грекова)
The objective of this study was to conduct comparative analysis of the immediate and long-term results of laparoscopic inguinal hernioplasty performed with and without fixation of the mesh endoprosthesis.Methods and materials. The base group included 77 patients who underwent laparoscopic inguinal hernioplasty without fixation of the mesh by herniostepler. The control group included 76 patients who underwent laparoscopic inguinal hernioplasty with mesh fixation by herniostepler. To assess the postoperative period, the following criteria were studied: the severity of postoperative pain on a Visual Analog Scale; postoperative complications on the Clavien-Dindo scale; an early recurrence of inguinal hernias determined by ultrasound.Results. In both groups, the severity of postoperative complications did not exceed grade I. Among the entire list of complications, there were observed: pain in the area of surgery, an increase in body temperature above 38.5 °C, acute urinary retention, swelling and hematoma of the scrotum, seroma. There were no cases of conversion, intraoperative damage to internal organs and vascular structures. Complications in both groups do not differ significantly and do not depend on the method of laparoscopic inguinal hernioplasty: with fixation of the endoprosthesis by herniostepler or without fixation. The level of pain in the early postoperative period in patients operated by laparoscopic inguinal hernioplasty with mesh fixation was significantly higher. During control examinations of patients on the day after surgery, at the time of discharge and 6 months after surgery, no cases of dislocation of mesh endoprosthesis and relapse of inguinal hernia were detected.Conclusion. The obtained data indicate the effectiveness of laparoscopic hernioplasty in inguinal hernias with polypropylene mesh without fixing with herniostepler.